2015
DOI: 10.1371/journal.pone.0118390
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Geographic Variation in Distribution and Abundance of Australian Deep-Water Kelp Forests

Abstract: Despite the significance of marine habitat-forming organisms, little is known about their large-scale distribution and abundance in deeper waters, where they are difficult to access. Such information is necessary to develop sound conservation and management strategies. Kelps are main habitat-formers in temperate reefs worldwide; however, these habitats are highly sensitive to environmental change. The kelp Ecklonia radiate is the major habitat-forming organism on subtidal reefs in temperate Australia. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 57 publications
(82 reference statements)
2
68
1
Order By: Relevance
“…These currents play an important role in the connectivity of larvae and propagules throughout the GSR (Condie et al 2005;Coleman et al 2011) and maintain relatively stable climatic conditions over seasonal and evolutionary time scales (McGowran et al 1997;Condie and Dunn 2006). Interestingly, however, although many species are shared between the eastern and western GSR, such as the dominant habitat-forming kelp Ecklonia radiata (Connell and Irving 2008;Marzinelli et al 2015), these regions have been connected through the Bass Strait for only ,10 000 years (Waters 2008) and still have low genetic connectivity (Waters 2008;Coleman et al 2013) and distinct biogeographical affinities (Waters et al 2010).…”
Section: The Ecological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…These currents play an important role in the connectivity of larvae and propagules throughout the GSR (Condie et al 2005;Coleman et al 2011) and maintain relatively stable climatic conditions over seasonal and evolutionary time scales (McGowran et al 1997;Condie and Dunn 2006). Interestingly, however, although many species are shared between the eastern and western GSR, such as the dominant habitat-forming kelp Ecklonia radiata (Connell and Irving 2008;Marzinelli et al 2015), these regions have been connected through the Bass Strait for only ,10 000 years (Waters 2008) and still have low genetic connectivity (Waters 2008;Coleman et al 2013) and distinct biogeographical affinities (Waters et al 2010).…”
Section: The Ecological Settingmentioning
confidence: 99%
“…Worldwide, where enough light penetrates to the seafloor, healthy temperate reefs are usually dominated by 'kelp forests' -highly productive, structurally complex communities of canopy-forming seaweeds of the orders Laminariales, Desmarestiales and Fucales (Bolton 2010;Steneck and Johnson 2013). Depending on light, waves and grazers, kelp forests are found from the shoreline down to depths of 30-40 m (Marzinelli et al 2015), but can be found at depths .60 m in some regions (e.g. Graham et al 2007).…”
mentioning
confidence: 99%
“…We could not clearly relate these local trends with the environmental variables considered in our study. However, in southern Queensland, the coastal environment is driven by the presence of a local upwelling, which allows for the northernmost temperate kelp beds to thrive around Henderson Island at the survey site (described by Marzinelli et al 2015). The reduced cover of fauna at Long Bay's surveyed sites might be related to the proximity of Long Bay to the heavily populated urban area of Sydney, and the bay itself having a history of significant sewerage pollution and concomitant effects on water quality (Sydney Water 2007).…”
Section: Physical Factors Associated With Small-scale Variation In Comentioning
confidence: 99%
“…Because ε 1 , ε 2 , ε 3 , ε 4 and ε 1 , ε 2 , ε 3 , ε 4 are all bounded, expression (34) implies that V is bounded. Hence, the application of Barbalat's Lemma [52] can prove that ε 1 , ε 2 , ε 3 , and ε 4 converge to zero as t → ∞.…”
Section: Controller Designmentioning
confidence: 99%
“…For many years, the scientific, commercial, and naval sectors have shown considerable interest in the design and development of unmanned marine vehicles (UMVs), which can be used to perform a multitude of different tasks, such as mineral resources sampling, offshore oil and gas operations, ocean engineering maintenance, and military reconnaissance [1][2][3][4]. As described in [5], UMV is usually used as a generic term to describe unmanned/autonomous underwater vehicles (UUV/AUV) and unmanned/uninhabited surface vessels (USV).…”
Section: Introductionmentioning
confidence: 99%